Back to Bataan - RKO Radio Pictures; Turner Entertainment Co.; Warner Home Video (Firm). (Burbank, Calif. Turner Entertainment Co., 2007)
After the fall of the Philippines in WWII, Colonel Joseph Madden of the U.S. Army stays on to organize guerrilla fighters against the conquerors.
In English with English, French, and Spanish subtitles.
Title from container.
Originally released as a motion picture in 1945.
Performers, John Wayne, Anthony Quinn, Beulah Bondi, Ben Barzman, Richard Landau, Edward Dmytryk.
DVD videos.
Keywords: War films; Films for the hearing impaired; Bataan, Battle of, Philippines, 1942.